Spinning Them Off: Entrepreneuring Practices in Corporate Spin-Offs - Katja Maria Hydle; Kjersti Vikse Meland (Journal of Entrepreneurship, Management and Innovation)

(untitled)
This paper focuses on the practices between parent and child firms in corporate spinoffs. We uncover the enacted aspects of knowledge, called knowing, through theories from seven cases of incumbent-backed spin-offs and find that the management of the parent firms are highly involved in the spin-offs. The practices associated with spinning off are solving problems, involving multidisciplinary expertise and entrepreneuring management at the parent firm. We contribute to the spin-off literature by discussing the knowledge required for successfully spinning off child firms and to practice theory by empirically uncovering the practical understanding involved in the origin and perpetuation of an organization.